Molecular biology of the cell - Alberts, Bruce (New York : Garland Publishing, 1989)
The hallmark features of Molecular Biology of the Cell have been retained, such as its consistent and comprehensive art program, clear concept headings, and succinct section summaries.
Introduction to the cell -- The molecular organization of cells -- From cells to multicellular organisms.
Includes bibliographical references and index.
Keywords: MOLECULAR BIOLOGY